Hot sheet : sweet and savory sheet pan recipes for every day and celebrations - Massov, Olga; Lemoine, Sanaë (Harvest, an imprint of William Morrow, 2024)
"Transform everyday meals into extraordinary ones, with more than 100 recipes harnessing the power of your sheet pan, including breakfasts, starters, dinners, and desserts. Say goodbye to boring food and hello to flavor-packed dishes for weeknight dining as well as special occasions"--